Analysis and experimental investigation on the flow rate controller for PWR accumulator. (October 2022) - Lu, Donghua; Wang, Kuo; Su, Qianhua; Xing, Jun; Peng, Fan
Highlights: The CFD calculation found the pressure difference mainly exists near the outlet pipe and this finding makes the scaling easy for the flow rate controller. The scaling law was derived in the paper and the similarity of the FRC was established by a set of criteria. Using air instead of the Nitrogen gas for the experiment was analyzed and the difference was little. Abstract: During the large break loss coolant accident (LBLOCA), the emergency safety injection system is used to inject the safety water into the reactor pressure vessel (RPV) via the primary circuit or direct vessel injection (DVI) to avoid any uncovering of the core. The accumulator (ACC) is an important device to act as a water supplier during the safety injection. A flow rate controller (FRC) was designed to provide the large-flow-rate injection to reflood core quickly at the beginning of the injection and then turn to the small-flow-rate injection later. It makes the safety injection longer than those normal ACCs with large flow rate only and improve the efficiency of the safety injection. A FRC concept was evaluated with computational fluid dynamics (CFD) software in the paper. The fluid flow pattern of the fast mode and slow mode were investigated to reveal the mechanism of the FRC operation. To perform the experiment on a small test section, a scaling analysis was done to find the criteria between the model and the prototype. Then a test facility was established to simulate the operation condition of the FRC based on the scaling results. A test section was tested in transient condition with 1/4 diameter and equal height of the prototype. The results show the flow rate ratio was 3.57:1 at the critical point of the flow rate. The paper also presents the thermal hydraulic parameters such as pressure, injection rate, liquid level, temperature of the gas and water in transient during the injection. The flow resistance coefficients of the two modes were obtained in the experiment too.